Osteochondritis dissecans of the elbow: state of the art. Issue 1 (10th January 2017) - Eygendaal, Denise; Bain, Gregory; Pederzini, Luigi; Poehling, Gary
Abstract : Osteochondritis dissecans (OCD) of the elbow is localised most commonly at the capitellum. It is a localised condition of the subchondral bone which may result in segmentation and separation. Irreversible changes, pain, restriction of motion and limitation of activities may result because of this. Elbow OCD afflicts athletes in the second decade, especially adolescents engaged in repetitive elbow overuse such as gymnasts, pitchers and swimmers. A high index of suspicion is warranted to prevent delay in the diagnosis. Imaging studies begin with standard elbow radiographs, but in later stages MRI or CT scan are indicated. Lesions are classified as 'stable' or 'unstable'. In general stable lesions are treated conservatively, whereas unstable lesions are indicated for surgical management. Geographical variation exists in techniques for arthroscopic procedures for OCD of the elbow. In Europe and the USA most surgeons use classic arthroscopic debridement and microfracturing for lesions which are not amendable to a solid fixation, whereas in Australia some surgeons use dry arthroscopy for optimal assessment of the articular surface and the presence or absence of subchondral bone. In Japan fixation of the OCD with bone pegs is favoured. Numerous other surgical techniques have been reported, including internal fixation of large fragments and osteochondral autograft transfer. The aim of this article is to explore OCD of the elbow with regard to aetiology, clinical presentation, the diagnostics prior to the intervention, the different surgical techniques, possible complications and pitfalls, clinical outcome and future directions.